An examination of referrals declined for chronic pain care: There is increasing mental health complexity within care-seeking patients with chronic pain over time - Rachael Bosma; Brittany N. Rosenbloom; Emeralda Burke; Christian Aquino; Cara Stanley; Kimberly Coombs; Adriano Nella; Shamalla James; Hance Clarke; David Flamer; Anuj Bhatia; John Flannery; et al. (Taylor & Francis Group, 2024)
Background Chronic pain is a complex disease that requires interprofessional care for effective management. Despite the need for multidisciplinary care, disease and health care inequities can prevent individuals from attaining adequate treatment. Factors such as mental health, cost, and distance to a health care center can contribute to health care accessibility inequality. The aim of this study is to examine declined referrals at the Toronto Academic Pain Medicine Institute (TAPMI) to determine the reason for declining care and number of declined referrals.Methods A retrospective chart review of all declined referrals at TAPMI in 2018 and 2022 was conducted. Referral documentation and the intake decision were extracted from the electronic medical charts by the research team and verified by the clinical intake team. Chi-square tests were conducted to determine whether the proportion of declined referrals changed between the years reviewed.Results The number of declined referrals due to mental health complexities increased significantly from 51 (11%) in 2018 to 180 (18%) in 2022 (χ2 = 10.9, P = 0.0009). A significant rise in the number of declines due to mental health service requests was also observed (χ2 = 24.53, P < 0.00001). Other common reasons for declined referrals in 2018 and 2022 included duplicate service, no primary care provider, and health care service changes.Conclusion Mental health complexities continue to be a significant barrier to health care service acquisition for individuals living with chronic pain. The increase in patient complexity from 2018 to 2022 highlights the need for integrated health care resources.